The different response of sugarcane genotypes in multiple stress - de Sousa, Francisco Bruno Ferreira [UNESP]; Cazetta, Jairo Osvaldo [UNESP]; Nascimento, Sabrina da Silva [UNESP] (FapUNIFESP (SciELO), 2018)
Research focused on identify abiotic stress-tolerant genotypes is highly desirable since their use may reduce costs of soil and crop management and productivity losses. The aim of this study was to determine the behavior of 24 sugarcane genotypes under high levels of Al 3+ and Mn 2+ associated with low availability of mineral nutrients. The experiment was carried out under greenhouse condition in a 24 × 2 factorial scheme (24 genotypes × 2 treatments: with and without stress), and four replications in completely randomized design. In the treatment without stress plants were grown in a complete nutrient solution whereas in the treatment with stress a nutrient solution with a high acidity (4.0 ± 0.1) and 5% of its original concentration, as well as a high concentration of aluminum (60 mg L -1 ) and manganese (700 mg L -1 ) was used. The genotypes RB966928, RB855443, IACSP96-3060, SP81-3250, RB867515, CTC 21, RB965902, and IAC91-1099 had their biometric characteristics less affected by the stress, possibly due to the ability to continue the process of cell division and elongation and to maintain meristematic viable regions, hence they were considered as the most tolerant. On the other hand, the genotypes RB965917, CTC 15, CTC17, RB855536, CTC 2, CTC 20, and CTC99-1906 were the most sensitive to stress. Root system was the most affected by stress, with most genotypes showing more than 70% reduction in root biomass. No relationship was observed between tolerance level of genotypes and the maturation cycles.
Diferente resposta de genótipos de cana-de-açúcar em múltiplo estresse
Keywords: Abiotic stress; Greenhouse; Hydroponic alternative system; Saccharum spp